The Relationship Between Philanthropic Foundation Funding and State-Level Policy in the Era of Welfare Reform. (December 2015) - Mosley, Jennifer E.; Galaskiewicz, Joseph
Philanthropic foundations play important symbolic and leadership roles in public policy debates by conferring legitimacy upon specific social problems and policy solutions, but little is known about how they respond to policy change and the roles they adopt in relationship to government. We investigate the degree to which foundations are responsive to the policy environment and ask whether they adopt roles consistent with meeting social needs, promoting social innovation, or both. We also investigate how these roles vary by foundation type (independent, community, corporate) and size. Longitudinal data on grants made by more than 1, 000 U.S. foundations during the welfare reform era of 1993-2001 show that during this time foundation grants were not responsive to population need; grants to safety net and social service programs did not increase. Large foundations and independent foundations focused on social innovation by funding research and workforce development and giving more in states pursuing policy innovation.